(untitled) (Eurasian Scientific Herald, 2022)
A comparative analysis of left ventricular systolic dysfunction and heart failure with preserved left ventricular ejection fraction was carried out. 69 patients with heart failure FC III–IV according to NYHA were examined. In the group of chronic heart failure with preserved ejection fraction (40% of patients), women predominate, older people with a significantly higher body mass index, suffering from diabetes mellitus, anemia. In these patients, creatinine and cholesterol levels are significantly higher, and hemoglobin levels are significantly lower than in patients with left ventricular systolic dysfunction